1994
DOI: 10.1128/mcb.14.2.1500
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of the human interferon regulatory factor 1 (IRF-1) and IRF-2 genes: implications for a gene network in the interferon system.

Abstract: Interferon regulatory factor 1 (IRF-1) and IRF-2 are structurally similar DNA-binding factors which were originally identified as regulators of the type I interferon (IFN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
168
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(181 citation statements)
references
References 59 publications
11
168
2
Order By: Relevance
“…This subtle level of regulation is also a ected by alterations in the IRF-1 : IRF-2 ratio during the cell cycle. In accord with previous observations demonstrating that an IRFbinding site is present in the IRF-2 promoter and that expression of IRF-2 gene is a ected by IRF-1 expression (Harada et al, 1994b), we showed that IRF-1 induced by IFN-g is able to bind to the IRF binding site present in the IRF-2 promoter and stimulate its transcription in both erythroid (Figure 4) and ®broblastic cells (not shown). Kinetic studies on the IRF-1 and IRF-2 mRNA accumulation after IFN-g treatment ( Figure 5) further support the observation that induction of IRF-2 by IFNs or virus infection is mediated by IRF-1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This subtle level of regulation is also a ected by alterations in the IRF-1 : IRF-2 ratio during the cell cycle. In accord with previous observations demonstrating that an IRFbinding site is present in the IRF-2 promoter and that expression of IRF-2 gene is a ected by IRF-1 expression (Harada et al, 1994b), we showed that IRF-1 induced by IFN-g is able to bind to the IRF binding site present in the IRF-2 promoter and stimulate its transcription in both erythroid (Figure 4) and ®broblastic cells (not shown). Kinetic studies on the IRF-1 and IRF-2 mRNA accumulation after IFN-g treatment ( Figure 5) further support the observation that induction of IRF-2 by IFNs or virus infection is mediated by IRF-1.…”
Section: Discussionsupporting
confidence: 92%
“…Inhibitory feedback mechanism of IRF-1 through the induction of IRF-2 Since IFN-g is able to induce both IRF-1 and IRF-2 with di erent kinetics (see following results in Figure 5) and a potential IRF site has been described within the IRF-2 promoter (Harada et al, 1994b) we sought to examine if IRF-1 produced in IFN-g treated cells was able to bind to its consensus binding site in the IRF-2 promoter. Cell extracts from 3Cl8 cells at di erent times of IFN-g treatment were incubated with doublestranded radiolabeled oligonucleotide corresponding to the IRF-1 consensus binding site in the IRF-2 promoter and the complexes formed were analysed by EMSA.…”
Section: Resultsmentioning
confidence: 99%
“…One putative site (GGGGGATTTCCAGC) for the NF-B transcription factor was found in CaIRF-2 5 flanking region. It matches the classical NF-B binding site consensus GGGRNNYYCC (R = A/G, Y = T/C) and is completely consistent with one site found in the 5 flanking region of human IRF-2 (Harada et al, 1994). Moreover, one ISRE-like site of CaIRF-1 was found in the start of transcription in CaIRF-2 gene.…”
Section: Discussionsupporting
confidence: 82%
“…The genome organization of CaIRF-1 and CaIRF-2 are very similar to that of human IRF-1 and IRF-2, but more compact (Harada et al, 1994). Comparison of exon-intron organization of human and snakehead IRF-1 and IRF-2 genes indicated a common evolutionary structure, notably within the exons encoding the DBD of the two factors.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation